Special Education Teachers’ Perceived Self-Efficacy in Teaching Students with Disabilities in Sultanate of Oman and United Arab Emirates - Haj Hussien, Jalal; Al-Shayeb, Abdelhafez; Al-Qaryouti, Ibrahim (Jordan Journal of Educational Sciences, 2016)
The purpose of the current study was to investigate the level of self-efficacy of special education teachers in teaching students with disabilities in inclusive classrooms. The relationship between the level of self-efficacy and these selected variables: gender, country, teaching experience, and school level taught were examined. Also, the variation of the level of self-efficacy according to the domain of knowledge and skills was examined. Five hundred and thirteen special education teachers from Oman and the UAE participated in the study. The Special Education Teachers’ Perceived Self-Efficacy Scale was used to collect data for this study after verifying the construct validity. The findings showed that the teachers perceived their self-efficacy as being efficient in all scale domains except the formal assessment domain. The findings also showed special education teachers’ country, gender, and school level taught significantly correlated with their self-efficacy in particular domains of knowledge and skills. Finally, the findings indicated that the level of self-efficacy of special education teachers varies according to the domain of knowledge and skills